Mate Marote: a BigData platform for massive scale educational interventions - Belloli, Laouen (2016)
In this paper we present Mate Marote, a web platform for massive scale educational interventions. We focus on the scaling requirements needed on these kind of deployments. We show the designed architecture, how these decisions solve the imposed requirements and the implementation. To test this development, we performed a small pilot intervention where the whole system was evaluated. We conclude that Mate Marote is ready for production deployment and enabled to middleto- massive scale interventions. For this purpose, we have deployed this platform in CEIBAL program at Uruguay with more than 100K potential users.